The Impact of Consecutive Tropical Cyclones on Changes in Environmental Factors and Phytoplankton Distributions in Overlapping Areas - Ying Chen; Hui Zhao; Hui Gao (Remote Sensing)
Tropical cyclones are known to have significant ecological impacts, particularly on marine productivity. This study investigates the effects of two tropical cyclones (TC “MARIA” and TC “AMPIL”) on changes in environmental factors and phytoplankton in overlapping marine areas during August 2024. Our findings indicated that TC “MARIA”, despite its lower wind speeds, resulted in significant increases in surface chlorophyll-a (Chl-a) due to its prolonged duration, while depth-integrated Chl-a showed a declining trend, suggesting limitations on phytoplankton growth due to water column instability and reduced light availability. In contrast, TC “AMPIL”, with its higher wind speeds and faster translation speed, caused more immediate disturbances, leading to increases in surface Chl-a. However, the depth-integrated Chl-a did not significantly increase, as phytoplankton growth was hindered by the succession of the two typhoons. Additionally, we observed a pronounced cooling in sea surface temperature after both typhoons, likely linked to ongoing mixing processes and atmospheric influences. This study can provide us with more insights into the interaction between tropical cyclone dynamics and marine ecology.